Implementation of Virtual Banking in E-Commerce Sales of Jamu Products - Tri Listyorini; Etika Kartikadarma; Devva Ricovani Susanto (Universitas Dharma Wacana, 2022)
Herbal medicine is familiar in the world of health, because there are no side effects if processed correctly. In Kudus, there are SMEs that process Klanceng into various health drinks, namely CV Jamu Klanceng. Marketing of Jamu Klanceng is still manual, namely opening outlets for sales. In addition, relying on sales to promote products from Jamu Klanceng. This technique causes sales of Jamu Klanceng to gradually decline, eroded by sales that have utilized information technology. This research combines information technology to play a role in marketing this product from Jamu Klanceng. The system to be built is based on a website, where payments are made using virtual banking. With this kind of payment, you avoid fraudulent orders and scams that often occur in this online era. The method in this study uses the waterfall method. Data collection is by conducting interviews and observations to CV Jamu Klanceng. In this research the design is compiled using a flow chart, which serves to design the system to fit the existing flow. This design uses Entity Relationship Diagram, Data Flow Diagram and relations between tables. The next step is to implement the design into the Hypertext Pre-processors programming language and use the MySQL database. The system that was built made the marketing and sales of Jamu Klanceng efficient and effective. There is no limit on sales as long as stock lasts, orders can be made for 24 hours. Unlike offline selling, there are time and effort limits.